Interventions for Depression Symptoms Among Adolescent Survivors of War and Displacement in Northern Uganda: A Randomized Controlled Trial - Bolton, Paul; Bass, Judith; Betancourt, Theresa; Speelman, Liesbeth; Onyango, Grace; Clougherty, Kathleen F.; Neugebauer, Richard; Murray, Laura; Verdeli, Helen (Jama, 2007)
Prior qualitative work with internally displaced persons in war-affected northern Uganda showed significant mental health and psychosocial problems. Objective To assess effect of locally feasible interventions on depression, anxiety, and conduct problem symptoms among adolescent survivors of war and displacement in northern Uganda. Design, Setting, and Participants A randomized controlled trial from May 2005 through December 2005 of 314 adolescents (aged 14-17 years) in 2 camps for internally displaced persons in northern Uganda. Interventions Locally developed screening tools assessed the effectiveness of interventions in reducing symptoms of depression and anxiety, ameliorating conduct problems, and improving function among those who met study criteria and were randomly allocated (105, psychotherapy-based intervention [group interpersonal psychotherapy]; 105, activity-based intervention [creative play]; 104, wait-control group [individuals wait listed to receive treatment at study end]). Intervention groups met weekly for 16 weeks. Participants and controls were reassessed at end of study. Main Outcome Measures Primary measure was a decrease in score (denoting improvement) on a depression symptom scale. Secondary measures were improvements in scores on anxiety, conduct problem symptoms, and function scales. Depression, anxiety, and conduct problems were assessed using the Acholi Psychosocial Assessment Instrument with a minimum score of 32 as the lower limit for clinically significant symptoms (maximum scale score, 105). Results Difference in change in adjusted mean score for depression symptoms between group interpersonal psychotherapy and control groups was 9.79 points (95% confidence interval [CI], 1.66-17.93). Girls receiving group interpersonal psychotherapy showed substantial and significant improvement in depression symptoms compared with controls (12.61 points; 95% CI, 2.09-23.14). Improvement among boys was not statistically significant (5.72 points; 95% CI, −1.86 to 13.30). Creative play showed no effect on depression severity (−2.51 points; 95% CI, −11.42 to 6.39). There were no statistically different improvements in anxiety in either intervention group. Neither intervention improved conduct problem or function scores. Conclusions Both interventions were locally feasible. Group interpersonal psychotherapy was effective for depression symptoms among adolescent girls affected by war and displacement. Other interventions should be investigated to assist adolescent boys in this population who have symptoms of depression.
Keywords: Depression Symptoms; Adolescent Survivors; War; Displacement